Home interventions are effective at decreasing indoor nitrogen dioxide concentrations. (11th January 2014) - Paulin, L. M.; Diette, G. B.; Scott, M.; McCormack, M. C.; Matsui, E. C.; Curtin‐Brosnan, J.; Williams, D. L.; Kidd‐Taylor, A.; Shea, M.; Breysse, P. N.; Hansel, N. N.
Abstract Nitrogen dioxide (NO2), a by‐product of combustion produced by indoor gas appliances such as cooking stoves, is associated with respiratory symptoms in those with obstructive airways disease. We conducted a three‐armed randomized trial to evaluate the efficacy of interventions aimed at reducing indoor NO2 concentrations in homes with unvented gas stoves: (i) replacement of existing gas stove with electric stove; (ii) installation of ventilation hood over existing gas stove; and (iii) placement of air purifiers with high‐efficiency particulate air (HEPA) and carbon filters. Home inspection and NO2 monitoring were conducted at 1 week pre‐intervention and at 1 week and 3 months post‐intervention. Stove replacement resulted in a 51% and 42% decrease in median NO2 concentration at 3 months of follow‐up in the kitchen and bedroom, respectively (P = 0.01, P = 0.01); air purifier placement resulted in an immediate decrease in median NO2 concentration in the kitchen (27%, P < 0.01) and bedroom (22%, P = 0.02), but at 3 months, a significant reduction was seen only in the kitchen (20%, P = 0.05). NO2 concentrations in the kitchen and bedroom did not significantly change following ventilation hood installation. Replacing unvented gas stoves with electric stoves or placement of air purifiers with HEPA and carbon filters can decrease indoor NO2 concentrations in urban homes.